Panama : 2017 Article IV Consultation-Press Release; and Staff Report for Panama. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Panama's economy as the fastest growing in Latin America over the past two decades. It is expected to remain among the most dynamic in the region, with stable and low inflation, sustainable public debt, a declining current account deficit, and a stable financial sector. Economic growth moderated to 4.9 percent in 2016 in the face of external headwinds, and inflation and unemployment remain subdued but have risen slightly. Fiscal consolidation continues in line with fiscal rule targets, and public debt is sustainable. Credit growth remains strong, but has begun to slow recently. The outlook is favorable despite heightened external uncertainty.